Analysis of Students' Difficulties in Learning Mathematics on Integer Topics in Grade 7 of MTs Ashhabul Yamin Academic Year 2022/2023 - Desi, Desi Andriani; Rusdi; Aniswita; Risnawita (BiCED Proceeding, 2025)
This research was motivated by the large number of students who had difficulty in understanding integer material. This is seen from the students' daily assignments given and interviews. This is because students do not know the whole of the integer material presented by the teacher, students do not know the material presented so they think that integer material is difficult material. The aim of this research is to describe the participants' difficulties in learning mathematics. Students form the 7th grade of MTsS Ashabul Yamin will be the informant in this research.The type of research used is qualitative narrative. The techniques used in collecting data are tests, interviews and documentation. The data analysis used is the Miles and Huberman model which consists of three steps, namely data reduction, data presentation and drawing conclusion. The research results showed that from 28 students who took the integer material test, there were only 6 students (21.43 %) who achieved the KKM score, while 22 students (78.57%) had not achieved the KKM score. Students' difficulties in learning mathematics in integer material are difficulties in counting, difficulties in repeating the material, difficulties in understanding the language of mathematics and difficulties in visual perception. So it can be concluded that there really are difficulties in students' learning mathematics in round number material in the 7th grade of MTsS Ashhabul Yamin.